Facile Preparation and Analytical Utility of ZnO/Date Palm Fiber Nanocomposites in Lead Removal from Environmental Water Samples - Basma G. Alhogbi; Ohowd Ibrahim; Mohamed Abdel Salam; Mohammed S. El-Shahawi; Mohammed Aslam (Molecules, 2022)
This study reports a facile approach for preparing low-cost, eco-friendly nanocomposites of ZnO nanoparticles (NPs) and date palm tree fiber (DPF) as a biomass sorbent. The hypothesis of this research work is the formation of an outstanding adsorbent based on the date palm fiber and ZnO nanoparticles. ZnO NP/DPF nanocomposites were synthesized by mixing the synthesized ZnO NPs and DPF in different mass ratios and evaluating their efficacy in adsorbing Pb2+ from aqueous solutions. The structure and surface morphology of the developed ZnO NP/DPF nanocomposite were critically characterized by XRD, FESEM, and TEM techniques. Compared to ZnO NPs, the ZnO NP/DPF nanocomposites displayed significantly enhanced Pb2+ uptake. Pb2+ adsorption was confirmed via various isotherm and kinetic models and thermodynamics. The computed Langmuir sorption capacity <semantics>(qm</semantics>) was found to be 88.76 mg/g (R2 > 0.998), and the pseudo-second-order R2 > 0.999 model was most appropriate for describing Pb2+ adsorption. Impregnating the biomass with ZnO NPs enhanced the spontaneity of the process, and the value (−56.55 kJ/mol) of <semantics>ΔH</semantics> displayed the exothermic characteristics of Pb2+ retention. Only the loaded ZnO NP/DPF achieved the removal of a high percentage (84.92%) of Pb2+ from the environmental water sample (seawater). This finding suggests the use of ZnO NP/DPF nanocomposites for removing heavy metals from environmental water samples to purify the samples.